Histórias de aprendizagem e sensibilidade à mudança nas contingências: efeito de instruções mínima, geral e específica - Vaz, Luiza Mulin (2017)
Behavioral analysts have been concerned with evaluating the effect of different learning histories over the sensitivity to the change of contingencies. The present research has investigated the effect of three variables over the sensitivity to the change of contingencies: (1) learning histories, by rules or contingencies; (2) the degree of instructional specificity (general instruction and specific instruction); and (3) maintenance or change of the instruction between phases. Twenty participants were assigned to one of five experimental groups, that were different by the acquirement of repertoire in Phase 1: two groups were exposure to general instruction; other two groups were exposure to specific instruction and one group were exposure to learning by contingencies (minimum instruction). In Phase 2, block 1, the same type of instruction was maintained for three groups; for the other two groups, the instruction was shifted to a minimum instruction. In Phase 2, block 2, the reinforcement contingency was modified without any previous warning. In both phases, a first order matching-to-sample task procedure was programmed in the computer. In Phase 1, was reinforced to choose one of the comparison stimuli that shared the property “equal in shape or in color” with the sample stimulus. This phase contained three sessions, of 36 trials each. Phase 2 contained three sessions, each divided into two blocks. Block 1 corresponded to the first 10 trials and Block 2 corresponded to the following 26 trials. In each block, a contingency would take effect. In blocks 1, there was instruction presentation and the contingency in effect was the same one of the Phase 1 (correct relation was the property: “equal in shape or in color”). In blocks 2, there was no instruction presentation and was reinforced to choose one of the comparison stimuli that did not shared any property with the sample stimulus. This change of contingencies occurred without previous warning. The results showed that the group exposed to learning by contingencies and one of the groups exposed to general instruction showed the most sensitivity when the contingencies were shifted. While one of the groups exposed to specific instruction showed insensitivity when the contingencies were shifted. This result indicates that learning histories by contingencies and by general instruction promotes the sensitivity to the change of contingencies. In the other hand, the learning history by specific instruction produces less sensitivity to the change of contingencies. In general, the groups that were exposed to minimal instruction in Phase 2 (blocks 1) showed more sensitivity to the change of contingencies when compared to the groups that were exposed to general or specific instruction between the two phases